Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
3 Answers
- ?Lv 75 years agoFavorite Answer
Well,
1) the result is obviously true for z=0
2) let z =/= 0
let' s use Euler's notation :
z = r e^(iθ) with r > 0 then we have the basic result : |z| = r
then :
z^n = r^n * [e^(iθ)]^n
= r^n * e^(inθ)
therefore :
|z^n| = |r^n * e^(inθ)|
= |r^n| * |e^(inθ)|
= |r^n| * 1
= r^n
= | z |^n
conclusion :
|z^n| = | z |^n
hope it' l lhelp !!
- ?Lv 75 years ago
lemma
|xz| = |x||z|
z = a + bi
and x = c + di
xz = (ac - bd) + (ad + cb) I
|z| = (a^2+ b^2)^1/2
|x| = (c^2 + d^2)^1/2
|x||z| = (a^2+ b^2)^1/2(c^2 + d^2)^1/2
= (a^2c^2 + a^2 d^2 + b^2c^2 + b^2d^2)
|xz| = ((ac - bd)^2 + (ad + cb)^2)^1/2
= (a^2 c^2 - 2 abcd + b^2d^2 + a^2 d^2 + 2 abcd + c^2 b^2)^1/2
= (a^2 c^2 + b^2d^2 + a^2 d^2 + c^2 b^2)^1/2
▪
|z| = |z|
suppose
|z^n| = |z|^n
|z^n+1| = |z z^n | = |z||z|^n = |z|^n+1
▪
- 5 years ago
Take z=x+iy so |z|^n is √(x+iy)^n similarly |z^n| is √(x+iy)^n hence proved. Hope it helped